2008
DOI: 10.4049/jimmunol.180.11.7423
|View full text |Cite
|
Sign up to set email alerts
|

Chronically Inflamed Human Tissues Are Infiltrated by Highly Differentiated Th17 Lymphocytes

Abstract: Chronic inflammatory diseases are characterized by local tissue injury caused by immunocompetent cells, in particular CD4+ T lymphocytes, that are involved in the pathogenesis of these disorders via the production of distinctive sets of cytokines. Here, we have characterized single CD4+ T cells that infiltrate inflamed tissue taken from patients with psoriasis, Crohn’s disease, rheumatoid arthritis, or allergic asthma. Results from a cytokine production and gene profile analysis identified a population of in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
368
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(392 citation statements)
references
References 41 publications
21
368
1
2
Order By: Relevance
“…These data suggest that CD4 ϩ T cells migrating into inflamed joints could be driven by direct interactions with activated monocytes toward a Th17 phenotype, and, thus, participate in the inflammatory response. Although it has previously been shown that Th17 cells and IL-17 are present at sites of human autoimmune inflammation, including RA (22)(23)(24), MS (25), and psoriasis (24,26), to our knowledge, it has not been demonstrated that APC taken from a site of inflammation can promote Th17 responses. As such, our data provide an insight into the formation of these highly pathogenic cells in vivo, and suggest that targeting of inflammatory monocytes could lead not only to a decrease in the production of proinflammatory cytokines, but also in a reduction in Th17 cells.…”
Section: Discussionmentioning
confidence: 90%
“…These data suggest that CD4 ϩ T cells migrating into inflamed joints could be driven by direct interactions with activated monocytes toward a Th17 phenotype, and, thus, participate in the inflammatory response. Although it has previously been shown that Th17 cells and IL-17 are present at sites of human autoimmune inflammation, including RA (22)(23)(24), MS (25), and psoriasis (24,26), to our knowledge, it has not been demonstrated that APC taken from a site of inflammation can promote Th17 responses. As such, our data provide an insight into the formation of these highly pathogenic cells in vivo, and suggest that targeting of inflammatory monocytes could lead not only to a decrease in the production of proinflammatory cytokines, but also in a reduction in Th17 cells.…”
Section: Discussionmentioning
confidence: 90%
“…We also included in our analysis Th1, Th2 and Th17 clones derived from chronically inflamed human tissues that were shown to be highly representative of T-cell polarization in humans. 24,27 This study involved 45 genes that have a pivotal role in CD4 pos T cell differentiation, localization and effector functions (Supplementary Table S1). The results of a principal component analysis revealed that FL and tonsil-derived T FH shared a very close gene expression signature, compared with Th1, Th2, Th17, Treg and FL T FR (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Th1, Th2 and Th17 clones were obtained from biopsies taken from active inflammatory lesions of patients suffering from chronic inflammatory or auto-immune diseases, as previously described. 24 Quantitative RT-PCR Total RNA was extracted using RNeasy Kit (Qiagen, Valencia, CA, USA). All samples used displayed an RNA integrity number of at least 9.4. cDNA was then generated using Superscript II reverse transcriptase (Invitrogen, Carlsbad, CA, USA).…”
Section: Cell Samplesmentioning
confidence: 99%
“…Research on allergic asthmatics has shown a significant increase in the percentage of Th17 cells in PBMCs and the plasma concentrations of IL-17 and IL-22, in proportion to the disease severity (7). This is supported by several studies in which increased IL-17A and IL-17F expression and Th17 cells in the tissues of asthmatics were observed (8)(9)(10). However, the role of Th17 cells in vascular remodeling in asthma remains to be elucidated.…”
mentioning
confidence: 87%